POLA KOMUNIKASI DRIVER GOJEK PEREMPUAN DALAM MEMENUHI KEBUTUHAN KELUARGA DI KOTA MAKASSAR - St Khadijah Tenripada P (UNIVERSITAS MUSLIM INDONESIA, 2020)
The aims of this research are: (1). To find out the communication patterns of female Gojek drivers in meeting the needs of families in the city of Makassar. (2) To find out the involvement of female Gojek drivers in meeting family needs. This research lasted for less than one month and is located in Makassar City. The research method used in this study is a qualitative research method. The informants in this study were four women who worked as Gojek online motorcycle taxis. Data collection techniques through observation, interviews, and documentation. The decision of a mother to work as an online motorcycle taxi driver in order to meet the primary needs of the family which is not fulfilled due to economic factors of course not only has a positive impact, but can also have a negative impact. Positive impact, working mothers can ease the family's economy in meeting needs. The negative impact is that working mothers lose a lot of time to interact and communicate with their husbands and children directly and are not always there when needed. The communication pattern of the informant and his family is the Primary Communication Pattern and uses verbal communication every day, in overcoming the problem of verbal communication more effectively because communication runs and occurs directly